Przesłanki ekonomiczne korygowania różnic w poziomie dochodów emerytalnych kobiet i mężczyzn w bazowych systemach emerytalnych typu ubezpieczeniowego - Ratajczak-Tuchołka, Joanna (The Economic Premises of Compensation of the Pension Level in the Social Insurance Systems, 2008)
The pension policy is a part of the state social policy and the pension system presents an important element of the social security system. In most of the EU-states, the crucial tier of the pension scheme, i.e. the basic one, is organized as the (social) insurance pension. It is characterized by a strong link between contributions and benefits. Insurance type pension schemes are typical for employee systems. Their construction causes the disproportion in the length of working phase to be reflected in the level of pension. As women usually retire earlier and their level of remuneration is generally lower compared to men, their base pension is also considerably lower. Because of the environment which determinates the individual factors of the pension provision (earnings and length of employment), the pension provision of women is far lower than of men. It can cause an important social problem. This raises some questions: if and why as well as in which areas (within or outside of the pension system) and how the compensation of the pension disparities of women and men could be done. In the article, the economic premises/circumstances, as one of four kinds of premises (the other are political, demographic, and cultural) of such decision were considered.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 405-412